2003
DOI: 10.1111/j.1443-1661.2004.00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Case of early gastric cancer with nodular gastritis

Abstract: A case of depressed early gastric cancer with nodular gastritis is described. A 47-year-old Japanese man was referred to our hospital and admitted for surgical treatment of gastric cancer. Barium upper gastrointestinal study and endoscopy examination showed a 4.5 × 3.0 cm depressed lesion with a deep central ulceration in the anterior wall of the lower corpus. An unusual miliary pattern resembling 'goose flesh' was observed endoscopically in the antrum. Biopsy specimens from the tumor showed poorly differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…In this study, six (5%) cases of gastric cancers, all of which were of the diffuse type, were observed in patients with NG. Previous reports indicate that NG is a risk factor for the development of diffuse‐type gastric cancer in the gastric corpus, and our results were in line with those of previous reports. NG appears to increase the risk of developing diffuse‐type cancer due to highly active gastric inflammation and lower levels of atrophy.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, six (5%) cases of gastric cancers, all of which were of the diffuse type, were observed in patients with NG. Previous reports indicate that NG is a risk factor for the development of diffuse‐type gastric cancer in the gastric corpus, and our results were in line with those of previous reports. NG appears to increase the risk of developing diffuse‐type cancer due to highly active gastric inflammation and lower levels of atrophy.…”
Section: Discussionsupporting
confidence: 94%
“…Observational studies of Japanese adults with NG have suggested an association with gastric cancer, particularly diffuse‐type gastric cancer . However, the biological and epidemiological associations between NG and cancer development are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Even though a close relationship between nodular gastritis and duodenal ulcer is reported, 7 a relationship between nodular gastritis with H. pylori infection and gastric cancer has been previously reported only by Miyamoto et al 13 . and Kamada et al 14 . In their reports, 13,14 six cases of gastric cancer with nodular gastritis showed the same characteristics: all gastric cancers were diagnosed histologically as the diffuse‐type and were located in the corpus with H. pylori infection (Figs 3,4).…”
Section: Association Between Nodular Gastritis and Gastric Cancermentioning
confidence: 95%
“…The histological features of nodular gastritis are hyperplasia of lymphoid follicles with germinal centers in the proper lamina of the stomach 2,3 . Since the discovery of Helicobacter pylori ( H. pylori ), several studies have shown nodular gastritis to be strongly associated with H. pylori infection, not only in children 2–11 but also in adults 11–15 …”
Section: Introductionmentioning
confidence: 99%
“…This is based on findings from 39 previous reports based on a PubMed search using the key words ''nodular gastritis'' and ''gastric cancer'' for articles published between 1966 and 2008, and ''Torihada-ien'' and ''Igan'' in the Igakuchuo Zasshi for published article in Japanese between 1983 and 2008 (Table 1) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The mean age of the patients was 34.1 years.…”
Section: Discussionmentioning
confidence: 99%